Talisia esculenta (A. ST.-HIL.) Radlk: physico-chemical characteristics, antioxidant activity and biological activity (Research, Society and Development, 2020)
Talisia esculenta (A. ST.-HIL.) Radlk is a Brazilian wild fruit, known as a pitomba, belonging to the Sapindaceae family. The objective of the present work was to perform a review of the literature in order to identify studies on its physico-chemical characterization, antioxidant activity and biological activity. The articles search was done in PubMed, SciELO, Science Direct and LILACS. We identified 90 publications, 8 in SciELO, 3 in LILACS, 67 in Science Direct and 12 in PubMed. Subsequently, duplication of the articles between the databases was verified, and the triage was done by reading the titles, abstracts and reading in full, to analyze which articles fit the study objective, and only 5 studies were included. The review exposes Talisia esculenta Radlk (A. ST.-HIL.) as a fruit that has a bioactive potential, but there is a shortage of studies that deal with its chemical composition and its biological activity.